Convergency of the fuzzy vectors in the pseudo-fuzzy vector space over Fp1(1) - Kweimei Wu (International Journal of Mathematics and Mathematical Sciences)
In 2003, we considered the pseudo-fuzzy vector space SFR over Fp1(1). Here, we further discuss the convergency of the fuzzy vectors in SFR.